2022
DOI: 10.1332/175795921x16324800210845
|View full text |Cite
|
Sign up to set email alerts
|

Incongruence between parental and adolescent educational aspirations hinders academic attainment

Abstract: Previous research has shown that parental educational aspirations for their children are an important predictor of children’s academic attainment. However, recent studies have pointed to potential negative effects, in particular if there is a mismatch between parental educational aspirations and the aspirations of their children. This study examines (1) the role of socio-demographic and school achievement–related factors in shaping a potential (mis)match between parental educational aspirations and the aspirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…With regards to grade aspirations, it is unclear what processes led students to strive for that specific grade. Their goal to receive a good grade might have formed due to pressure from their parents [57,58], which would represent the least autonomous type of extrinsic motivation ("external regulation") [7], but it might also have developed because the student found English to be an important language for communicating with people from different backgrounds, hence representing a much more autonomous type of extrinsic motivation ("integrated regulation"). Understanding these differences might also provide promising explanatory approaches as to why a person is more or less inclined to life-long learning and openness to necessary change.…”
Section: Relationships Between Perceived Competence and Motivationmentioning
confidence: 99%
“…With regards to grade aspirations, it is unclear what processes led students to strive for that specific grade. Their goal to receive a good grade might have formed due to pressure from their parents [57,58], which would represent the least autonomous type of extrinsic motivation ("external regulation") [7], but it might also have developed because the student found English to be an important language for communicating with people from different backgrounds, hence representing a much more autonomous type of extrinsic motivation ("integrated regulation"). Understanding these differences might also provide promising explanatory approaches as to why a person is more or less inclined to life-long learning and openness to necessary change.…”
Section: Relationships Between Perceived Competence and Motivationmentioning
confidence: 99%
“…Educational aspirations are expressed preferences on a spectrum of educational destinations that are typically arranged in order of difficulty. As it has been repeatedly shown that educational aspirations are predictive of future educational attain-SJS 49 (2), 2023, 339-366 ment (e. g., Beal and Crockett 2010;Bozick et al 2010;Schoon and Burger 2021), investigating how students adapt their aspirations upon leaving compulsory school is pertinent.…”
Section: Educational Aspirationsmentioning
confidence: 99%
“…Social influence has proved to be a viable factor in explaining educational aspirations. In particular, the role of parents has been repeatedly stressed: it is suggested that students align their educational aspirations with their parents ' expectations (e. g., Marjoribanks 2002;2003;Augustine 2017;Roth 2017;Forster 2021;Schoon and Burger 2021). While the influence of the family provides a baseline for the initial formation of educational aspirations, it is assumed that peers become an increasingly important source of influence during adolescence (Osterman 2000;Brechwald and Prinstein 2011).…”
Section: Theoretical Explanations For Educational Aspirationsmentioning
confidence: 99%
See 1 more Smart Citation